Investigating the use of speech recognition technique for telephone line quality assessment - 424482 Harithuddin Abd. Rahman (Skudai : Universiti Teknologi Malaysia, 2000)
Kertas Projek (Sarjana Muda Kejuruteraan Elektrik) - Universiti Teknologi Malaysia, 2000